Perspective on the Competitiveness of the Colombian Productive Sector, from Face to Internationalization (Global Journal of Management and Business Research, 2019)
This document seeks to contribute to the debate on Colombia's international competitiveness through a proposal that covers the economy as a whole, but that especially focuses on the Colombian manufacturing sector (as a generator of added value) and the economic environment in which they are immersed. Although, the importance of the firm, it is argued that the macroeconomic, sectoral and institutional factors are one of the main determinants of productivity achieved by firms, the added value and the competitive embed achieved in both the national and international markets. For this document, statistical and documentary information is used, from government agencies and various authors in order to contrast and support the above.
Keywords: colombia; manufacturing; industry; productivity; competitiveness; international trade policy